2021
DOI: 10.4047/jap.2021.13.4.258
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surface topography and roughness in different yttrium oxide compositions of dental zirconia after grinding and polishing

Abstract: PURPOSE The purpose of this study was to compare the surface roughness, phase transformation, and surface topography of dental zirconia with three different yttrium oxide compositions under same grinding and polishing conditions. MATERIALS AND METHODS Three zirconia disks (IPS e.max ZirCAD LT, MT, MT multi, Ivoclar Vivadent AG, Schaan, Liechtenstein) were selected for experimental materials. Sixty-nine bar-shaped specimens were fabricated as 12.0 × 6.0 × 4.0 mm using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Moreover, it was observed that all specimens mainly contained tetragonal phase with no phase transformation for either sintering mode regarding their crystalline composition. The XRD graphs corroborates with a previous study that investigated the same zirconia under different surface conditions, however they did used fast sintering protocols 21 . Another investigation has found 15 wt.% of cubic phase for the same zirconia; however the author crystalized the zirconia using 1500°C for 2 h 22 .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Moreover, it was observed that all specimens mainly contained tetragonal phase with no phase transformation for either sintering mode regarding their crystalline composition. The XRD graphs corroborates with a previous study that investigated the same zirconia under different surface conditions, however they did used fast sintering protocols 21 . Another investigation has found 15 wt.% of cubic phase for the same zirconia; however the author crystalized the zirconia using 1500°C for 2 h 22 .…”
Section: Discussionsupporting
confidence: 86%
“…The XRD graphs corroborates with a previous study that investigated the same zirconia under different surface conditions, however they did used fast sintering protocols. 21 Another investigation has found 15 wt.% of cubic phase for the same zirconia; however the author crystalized the zirconia using 1500 C for 2 h. 22 Other study showed low amounts of cubic phase for other 3Y-TZP materials: 8 wt.% for CEREC Zirconia sintered using a Speed sintering (15 min/2 min/1578 C) and 20 wt.% for inCoris TZI sintered using a conventional protocol (4 h/2 h/1510 C). 13 In addition, the authors found that the zirconia phase composition was influenced by sintering mode, since speed sintered zirconia presented more tetragonal phase (92.1%) than the conventionally sintered (80%).…”
Section: Staircase Fatigue Results and Failure Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the existing peaks compared with current studies, specimens from 5Y-PSZ showed a cubic phase whereas 3Y-TZP specimens showed a tetragonal structure. Only minimal phase changes for the 3Y-TZP specimens were detected [ 21 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…The plasma performance of these applications significantly depends on the experimental parameters, and one of the most important characteristics is the gas species. Conventional plasma sources are limited in their ability to generate gas; therefore, previous studies that experimented with the surface treatment of zirconia only used a few specific gases, including nitrogen, helium, and argon [13,14]. Additionally, the effect of irradiation time and the flow rate of plasma on the zirconia surface remains unclear [15].…”
Section: Introductionmentioning
confidence: 99%